A Study on the effectiveness of legal provisions on internal safety and health systems and practices of public sector organizations in Uganda - Kagawa, Peter (KDI School, 2011)
This thesis focused on the study of the effectiveness of legal provisions on internal safety and health systems and practices of the Public sector organizations of Uganda. Such legal provisions are enshrined in the Constitution and other laws such as the Occupational Health and Safety Act, 2006. Whereas the legal provisions meant to promote internal health and safety systems at work places are well spelt out, there is lack of strict adherence to those provisions by Public Service organizations in Uganda. Yet, at the global level, this area has attracted much attention because of the civil and crimina, penalties, including litigation costs that are associated with non-compliance. In this regard, recommendations have been provided to improve the implementation of the legal provisions on health and safety in the Public Sector. These, among others, include: consideration of budget items for health and safety activities, promotion of employee awareness, and monitoring of health and safety systems in Public sector work places.
Thesis(Master) --KDI School:Master of Public Policy,2011
Keywords: Uganda.